PELAYANAN PENDIDIKAN DASAR PADA SDLB NEGERI SUNGAI MALANG KECAMATAN AMUNTAI TENGAH KABUPATEN HULU SUNGAI UTARA - Ahmad Riduan (Jurnal PubBis, 2017)
Referring to the Preamble of Constitution of the Republic of Indonesia, every citizen entitled to a proper education is no exception to children with physical, mental-intellectual, social, and emotional disabilities commonly called Special Children (ALB) or Children with Special Needs (ABK). For them, special schools (SLB) from primary to intermediate level are the main hope for fulfillment of non-conventional education desires not obtained from other educational institutions. In SDLB Negeri Sungai Malang, the quality of basic education provided in general is sufficient enough to meet the thirst of education for students in terms of teachers, curriculum, academic atmosphere, and scientific resources. Behind that, there is a lack of discipline in the teacher's aspect, the lack of technology in the learning process in the curriculum aspect, the expansion of school land in the academic atmosphere aspect, and the lack of visual aids on the scientific aspect. In the future, it is necessary to improve the quality of education service in SDLB Negeri Sungai Malang by the Head of Education Office in Hulu Sungai Utara Regency through the expansion of school land of SDLB Negeri Sungai Malang for the fulfillment of academic atmosphere besides the provision of digital technology facilities and a number of props to support the learning process for ABK with the efforts of the Headmaster of SDLB Negeri Sungai Malang to improve teacher discipline through continuous direct/indirect supervision techniques and the use of electronic attendance (finger print) in addition to the exemplary performance of the Headmaster to the teachers. Keywords : Basic Education, Children with Special Needs, Quality of Public Service